Engaged ownership : a guide for owners of family businesses - Renkert-Thomas, Amelia, 1962- (Wiley, 2016)
"Successful ownership transition requires effective decision making at the top Engaged Ownership is the definitive owner's guide to the family enterprise. Whether you're taking over a family business, family office, or trust, this book shows you how to work effectively with the management and board to keep the enterprise moving in the right direction. The first guide of its kind written from the owner's perspective, this book is designed to help owners who are truly committed to growing all forms of capital be successful in their role. You'll learn the time-tested process that helps you 'unstick' decision-making, become engaged and effective, and manage the transfer from owner control to shared ownership while minimizing risk. Improve communication and relationships with the board, and ensure that every stakeholder understands your strategies and vision for the future. You'll allay the fears that frequently accompany ownership transfers, and inspire a sense of teamwork that leads to sustainable success generation after generation. As the Baby Boomers retire, business founders and entrepreneurs worldwide are transferring ownership of privately held enterprises to their children in record numbers. It can be a complex and difficult-to-navigate time for everyone involved. This book helps you smooth the way to a successful transition, and transcend the owner's traditionally passive role. Learn to work effectively with management and the board Get everyone on the same page in terms of vision and direction Build relationships that lead to forward-thinking decision making Succeed in the ownership role by bringing your expertise to the fore Ownership transfer often triggers a radical change in family enterprise, and if poorly managed, can turn a business in the wrong direction. Engaged Ownership shows you how to build a dynamic and effective partnership with trustees, board, and management, and become a successful steward of the family's financial, human, social, and operational capital"--